The Influence of Children's and Adolescent Literature in Indonesia in the Formation of Character: A Hermeneutic Study - Amanda Liviani Br Muham; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2024)
Children's and adolescent literature are two genres in literature that are different in terms of their goals, themes and writing. Children's and youth literature in Indonesia has become an interesting subject in literary studies. So, the aim of this research is to determine the influence of children's and youth literary works in forming character. This research uses a qualitative descriptive research design. Then the researcher carried out an analysis of fables in children's literature and novels in youth literature. The results of the research show that children's literature and youth literature have an influence on character formation. Literary works have many uses and benefits for life. Apart from that, literary works are useful because they can be a recreational means for readers and viewers, and the process of enjoying them will bring calm and maturity to the soul through studying the contents of literary works. In this way, the moral messages, attitudes, behavior and personality depicted in literary works will give rise to a full soul in them, which will ultimately lead the learner to change the character values of children and adolescents.